Voltage reference architectures for low-supply-voltage low-power applications. Issue 11 (November 2015) - Basyurt, Pinar Basak; Bonizzoni, Edoardo; Aksin, Devrim Yilmaz; Maloberti, Franco
Abstract: This paper presents a voltage reference generator architecture and two different realizations of it that have been fabricated within a standard 0.18 μm CMOS technology. The architecture takes the advantage of utilizing a sampled-data amplifier (SDA) to optimize the power consumption. The circuits achieve output voltages on the order of 190 mV with temperature coefficients of 43 ppm/°C and 52.5 ppm/°C over the temperature range of 0 to 120°C without any trimming with a 0.8 V single supply. The power consumptions of the circuits are less then 500 nW while occupying an area of 0.2 mm 2 and 0.08 mm 2, respectively.